Hemoptysis in Renal Transplant Recipients - Georgakopoulou, Vasiliki Epameinondas; Gkoufa, Aikaterini; Aravantinou, Aikaterini; Garmpis, Nikolaos; Mantzouranis, Konstantinos; Chlapoutakis, Serafeim; Sklapani, Pagona; Garmpi, Anna; Trakas, Nikolaos; Damaskos, Christos (Acta medica Lituanica, 2021)
Background: Hemoptysis is the expectoration of blood from respiratory system. Clinical entities associated with hemoptysis in renal transplant recipients differ from those causing hemoptysis in common population. This review summarizes all reported clinical conditions related to hemoptysis in renal transplant patients, their causes, diagnostic approach and management. Methods and Materials: Primary literature was researched through MEDLINE/PubMed database and Google Scholar without restrictions. Relevant and current literatures related to hemoptysis in renal transplant recipients were used. Results: Overall 23 articles were included, since they report clinical conditions associated with hemoptysis in renal transplant recipients. Opportunistic lung infections, pulmonary hemorrhage associated with drugs and malignancies are usual causes of hemoptysis in these patients, sometimes with a fatal outcome. Conclusions: Hemoptysis is an important manifestation in renal transplant patients, caused frequently by rare clinical entities, different from those in common population.